Code of Ethics, Clawback Incentive Schemes, and Personal Value to Mitigate Earnings Management Intention - Erlinda Nur Khasanah; Mahfud Sholihin (Journal of Accounting and Investment, 2020)
Research aims: This study aimed to examine the role of a code of ethics and clawback incentive schemes to mitigate earnings management intention. This study also examined the effect of personal value on the relationship between the code of ethics and incentive schemes with earnings management intention.Design/Methodology/Approach: The research method used in this study was an experimental approach with a factorial design of 2x3 between-subjects. The subjects were 83 students from the undergraduate and postgraduate of Accounting Program from a public university in Yogyakarta, Indonesia. To test the hypotheses, two-way ANOVA was used.Research findings: This study discovered that the code of ethics was able to mitigate earnings management intention. However, it should be completed by clear and strict sanctions for ethical violations. The results, however, showed that there were no significant different effects between clawback and bonus-only incentive schemes on earnings management intention. Additionally, this study provided empirical evidence that personal value did not moderate the relationship between the code of ethics and incentive schemes on earnings management intention.Theoretical contribution/Originality: This study showed the causality relationship between the code of ethics and incentive scheme with earnings management intention through the use of experimental methods.Practitioner/Policy implication: This study has important implications for company management in designing and implementing a code of ethics effectively, namely the company should provide sanctions for those who violate the code of ethics.Research limitation/Implication: First, this study only examined earnings management in the form of real earnings management as the operating decisions. Second, most of the data collection was carried out after class, causing participants to lack concentration as they were tired of the lessons in class.Keywords: Earnings Management Intention, Code of Ethics, Clawback Incentive Schemes, Personal Value